Déjà vu: a reappraisal of the taphonomy of quarry VM4 of the Early Pleistocene site of Venta Micena (Baza Basin, SE Spain) - Paul Palmqvist; M. Patrocinio Espigares; Juan A. Pérez-Claros; Borja Figueirido; Antonio Guerra-Merchán; Sergio Ros-Montoya; Guillermo Rodríguez-Gómez; José Manuel García-Aguilar; Alejandro Granados; Bienvenido Martínez-Navarro (Scientific Reports, 2022)
Abstract Venta Micena, an Early Pleistocene site of the Baza Basin (SE Spain), preserves a rich and diverse assemblage of large mammals. VM3, the main excavation quarry of the site, has been interpreted as a den of the giant hyaena Pachycrocuta brevirostris in the plain that surrounded the Baza palaeolake. Taphonomic analysis of VM3 has shown that the hyaenas scavenged the prey previously hunted by the hypercarnivores, transported their remains to the communal den, and consumed the skeletal parts according to their marrow contents and mineral density. In a recent paper (Luzón et al. in Sci Rep 11:13977, https://doi.org/10.1038/s41598-021-93261-1 , 2021), a small sample of remains unearthed from VM4, an excavation quarry ~ 350 m distant from VM3, is analysed. The authors indicate several differences in the taphonomic features of this assemblage with VM3, and even suggest that a different carnivore could have been the agent involved in the bone accumulation process. Here, we make a comparative analysis of both quarries and analyse more skeletal remains from VM4. Our results indicate that the assemblages are broadly similar in composition, except for slight differences in the frequency of megaherbivores, carnivores and equids according to NISP values (but not to MNI counts), the degree of bone weathering, and the intensity of bone processing by the hyaenas. Given that VM4 and VM3 were not coeval denning areas of P. brevirostris, these differences suggest that during the years when the skeletal remains were accumulated by the hyaenas at VM3, the rise of the water table of the Baza palaeolake that capped with limestone the bones was delayed compared to VM4, which resulted in their more in-depth consumption by the hyaenas.